2013
DOI: 10.2323/jgam.59.267
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism of action of plant growth-promoting rhizobacteria (PGPR) strain Bacillus pumilus WP8 via regulation of soil bacterial community structure

Abstract: According to the traditional view, establishment and maintenance of critical population densities in the rhizosphere was the premise of PGPR to exert growth-promoting effects. In light of the facts that soil bacterial community structures can be changed by some PGPR strains including Bacillus pumilus WP8, we hypothesize that regulation of soil bacterial community structure is one of the plant growth-promoting mechanisms of B. pumilus WP8, rather than depending on high-density cells in soil. In this study, dena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
5
29
0
Order By: Relevance
“…safensis strains, including the Type strain FO-36b(T) [ 41 ], were only found in Cluster III, we propose that the B . pumilus strains WP8 [ 5 ], B4134, B4107, CCMA-560 [ 42 ] and Fairview [ 43 ] should be renamed as B . safensis .…”
Section: Resultsmentioning
confidence: 99%
“…safensis strains, including the Type strain FO-36b(T) [ 41 ], were only found in Cluster III, we propose that the B . pumilus strains WP8 [ 5 ], B4134, B4107, CCMA-560 [ 42 ] and Fairview [ 43 ] should be renamed as B . safensis .…”
Section: Resultsmentioning
confidence: 99%
“…The direct effects of microbial inoculants promote plant growth had been extensively described ( Colla et al, 2015 ; Wang et al, 2017 ). Nowadays, some works had been suggested that regulation of soil bacterial community structure is one of the plant growth-promoting mechanisms of microbial inoculants ( Kang et al, 2013 ; Rodriguez-Caballero et al, 2017 ). Our results did support this opinion.…”
Section: Discussionmentioning
confidence: 99%
“… Kang et al (2013) suggested that Bacillus pumilus might not maintain a high density population in the rhizosphere, but that its presence might have a crucial long-term impact on the surrounding microbiome, which consequently affects plant growth. Since the quality and quantity of root exudate nutrients can differ with plant age, plant growth stage also impacts the composition and abundance of the rhizosphere microbial community ( Liu et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of complex roles of the microbial inoculants in the introduced rhizosphere, the effects of introduced PGPRs on the rhizosphere microbial communities are still controversial ( Kang et al, 2013 ). For example, Chowdhury et al (2013) reported that PGPRs cause minor changes in the microbial community and Kozdrój (2008) found that they cause significant shifts.…”
mentioning
confidence: 99%